2017
DOI: 10.1021/acs.inorgchem.6b02165
|View full text |Cite
|
Sign up to set email alerts
|

Copper Complexes as Bioinspired Models for Lytic Polysaccharide Monooxygenases

Abstract: We report here two copper complexes as first functional models for lytic polysaccharide monooxygenases, mononuclear copper-containing enzymes involved in recalcitrant polysaccharide breakdown. These complexes feature structural and spectroscopic properties similar to those of the enzyme. In addition, they catalyze oxidative cleavage of the model substrate p-nitrophenyl-β-d-glucopyranoside. More importantly, a particularly stable copper(II) hydroperoxide intermediate is detected in the reaction conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
49
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 38 publications
(53 citation statements)
references
References 23 publications
4
49
0
Order By: Relevance
“…269 In parallel, Concia et al showed that tridentate complexes with both N -[(1-methyl-1 H -imidazol-2-yl)-methylene]-2-pyridineethanamine (L AM ) and N -[(1-methyl-1 H -imidazol-2-yl)methylene]-2-pyridineethanimine (L IM ) produced stable Cu(II)–hydroperoxide complexes that react with a model substrate ( p -nitrophenyl- β -D-glycopyranoside) of cellulose at room temperature. 296 The role(s) of this intermediate, however, were not uncoupled from alternative scenarios involving copper-generated radicals. Regardless, these data provide insight into a potential mechanism for LPMO function where H 2 O 2 is utilized as a cosubstrate.…”
Section: Active Site Geometric and Electronic Structure And Molecumentioning
confidence: 99%
“…269 In parallel, Concia et al showed that tridentate complexes with both N -[(1-methyl-1 H -imidazol-2-yl)-methylene]-2-pyridineethanamine (L AM ) and N -[(1-methyl-1 H -imidazol-2-yl)methylene]-2-pyridineethanimine (L IM ) produced stable Cu(II)–hydroperoxide complexes that react with a model substrate ( p -nitrophenyl- β -D-glycopyranoside) of cellulose at room temperature. 296 The role(s) of this intermediate, however, were not uncoupled from alternative scenarios involving copper-generated radicals. Regardless, these data provide insight into a potential mechanism for LPMO function where H 2 O 2 is utilized as a cosubstrate.…”
Section: Active Site Geometric and Electronic Structure And Molecumentioning
confidence: 99%
“…Simaan has recently reported the LPMO-like reactivity of mononuclear Cu(II) complexes using H 2 O 2 as oxidant (Figure 35). 185 These copper complexes catalyzed the oxidative cleavage of 4-nitrophenyl- β - D -glucopyronaside via C–H oxidation of the 1-position of the glucose derivative to produce glucolactone and 4-NO 2 -phenolate (observed and quantified by UV–vis). It was suggested that the LCu II reacted with H 2 O 2 under aqueous conditions to form a mononuclear LCu II (OOH) species that could be characterized by UV–vis ( λ : 305 nm) and EPR spectroscopy.…”
Section: Bioinspired Cu-promoted Oxidation Of Substrates Using O2 (Ormentioning
confidence: 99%
“…For the solvated systems, solvent molecule is directly coordinated to the Cu(II)-centre along with two nitrates and two halopyridines thereby transforming the distorted octahedral to distorted pentagonal bipyramid geometry -a coordination geometry frequently reported for Cu(II)-complexes. [34][35][36][37][38] In the…”
Section: Coordination Geometry Analysismentioning
confidence: 99%